Rupture in the Legal Hierarchy: Normative Conflicts and the Subversion of Agrarian Principles in Indonesia’s Omnibus Law - Situmorang, Waldus; F. R., Mella Ismelina; Rasji, Rasji (UI Scholars Hub, 2024)
This article examines the normative conflict between Law No. 6 of 2023 on the Establishment of Government Regulation in Lieu of Law on Job Creation and the Basic Agrarian Law (UUPA), specifically within the land law cluster. Using a normative approach and the theory of derogation, the article identifies three core areas of legal inconsistency: (1) the strengthening of Land Management Rights (Hak Pengelolaan), (2) foreign ownership of apartment units, and (3) the granting of land rights in aboveground and underground spaces. These legal inconsistencies not only create normative dualism but also generate legal uncertainty and threaten the principle of the rule of law. The article discusses the legal and policy implications of this dualism and proposes pathways for harmonization, including affirming the UUPA as a lex specialis, revising sectoral laws, or filing for judicial review. The analysis ultimately seeks to reclaim coherence in Indonesia’s land governance framework amidst the rising trend of autocratic legalism in pro-investment legislation.